Genetic structure of the Greek olive germplasm revealed by RAPD, ISSR and SSR markers - Linos, Athanasios A.; Nikoloudakis, Nikolaos; Katsiotis, Andreas; Hagidimitriou, Marianna (My University, 2014)
The olive is globally considered as one of the most significant crops, with more than 1200 distinctive cultivars and an abundant number of wild forms. Greece, the third largest producer worldwide, has been considered a secondary centre of domestication and its genetic recourses are potentially valuable for olive breeding. In the current study, the genetic diversity of an extended Greek olive germplasm collection (101 accessions) was revealed using RAPD, ISSR and SSR markers in an attempt to explore the genetic relationships among them, and comprehend how genetic variability is partitioned between the Greek germplasm. A Bayesian model-based clustering method was employed and allocation of genotypes into defined gene pools according to genetic and geographic criteria was detected. Genealogies detected by Median-Joining coalescent simulations, classified all genotypes into a complex network. Both linear and reticulate ties among the Greek olive cultivars were revealed. Hence, data suggested that both sexual and vegetative propagation have contributed to the evolution of the Greek olive germplasm. Furthermore, clustering of olive cultivars was correlated to their primarily usage (table or oil producing) and fruit size. Finally, Greek olive cultivars are characterized providing a useful clarification on synonyms and homonyms, facilitating the identification of duplicates.
Keywords: Genetic diversity; In situ conservation; Molecular markers; Olea europaea; Olive germplasm